Impostorism and anxiety contribute to burnout among resident physicians. (3rd July 2022) - Liu, Rachel Q.; Davidson, Jacob; Van Hooren, Tamara A.; Van Koughnett, Julie Ann M.; Jones, Sarah; Ott, Michael C.
Abstract: Purpose: Physician burnout is an issue that has come to the forefront in the past decade. While many factors contribute to burnout the impact of impostorism and self-doubt has largely been ignored. We investigated the relationship of anxiety and impostorism to burnout in postgraduate medical learners. Materials and methods: Postgraduate learners in four diverse training programs: Family Medicine (FM), Paediatric Medicine (PM), Anesthesiology (AN), and General Surgery (GS) were surveyed to identify the incidence of impostorism (IP), anxiety, and burnout. IP, anxiety, and burnout were evaluated using the Clance Impostor Phenomenon Scale (CIPS), Maslach Burnout Inventory-Human Services Survey (MBI-HSS), and the General Anxiety Disorder-7 (GAD-7) questionnaires, respectively. Burnout was defined as meeting burnout criteria on all three domains. Relationships between IP, anxiety, and burnout were explored. Results: Two hundred and sixty-nine residents responded to the survey (response rate 18.8%). Respondents were distributed evenly between specialties (FM = 24.9%, PM = 33.1%, AN = 20.4%, GS = 21.6%). IP was identified in 62.7% of all participants. The average score on the CIPS was 66.4 ( SD  = 14.4), corresponding to 'frequent feelings of impostorism.' Female learners were at higher risk for IP (RR = 1.27, 95% CI: 1.03–1.57). Burnout, as defined by meeting burnout criteria on all three subscales, was detected in 23.3% of respondents. Significant differences were seen in burnout between specialties ( p  = 0.02). GS residents were more likely to experience burnout (31.7%) than PM and AN residents (26.7 and 10.0%, respectively, p  = 0.02). IP was an independent risk factor for both anxiety (RR = 3.64, 95% CI:1.96–6.76) and burnout (RR = 1.82, 95% CI: 1.07–3.08). Conclusions: Impostorism is commonly experienced by resident learners independent of specialty and contributes to learner anxiety and burnout. Supervisors and Program Directors must be aware of the prevalence of IP and the impact on burnout. Initiatives to mitigate IP may improve resident learner wellness and decrease burnout in postgraduate learners.